Efficacy of SEVISTA (Ormeloxifene) in treatment of mastalgia and fibrocystic breast disease - Bansal, Vandana; Bansal, Arpit; Bansal, Ashwani Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Mastalgia and fibrocystic breast disease is common in women. Ormeloxifene (SEVISTA) is a weak oestrogen receptor (ER) agonist, a strong ER antagonist (SERA) and therefore a selective ER modulator (SERM) used in the treatment of the disease. Aim of study was to see the efficacy of ormeloxifene in women with pain in breast associated with or without fibrocystic breast disease. Methods: This was a randomized control trial of oral ormeloxifene 30 mg alternate day for 3 month in patients of 20 – 50 years old with breast pain and fibrocystic (without cancer). The pain was accessed by visual analogue scale and nodularity grade on a 5 – point. Results: Total 203 patients were completed the study. The mean age was 32.8 ± 8.35 years. The mean pain level was continuously decrease over 5 visit (5.8 to 0.86) and there was significant improvement was observed in the nodularity grades i.e. at beginning of treatment 1 and 2 nodularity were seen in 62 (30.5%) patients where as grades 3, 4 and 5 were seen in 141(69.5%) and at the end of six month it was 188 (92.6%) patients had grades 1 and 2 and only 15 (7.4%) had grade 3, 4 and 5 nodularity. Conclusion: SEVISTA (Ormeloxifene) showed significant efficacy for the treatment of mastalgia and fibrocystic breast disease.